The provision of non-audit services, audit partner tenure, a new audit and auditor independence: Evidence from going concern opinions - Ramlan, Mohd Raime; Shafie, Rohami; Abdul Kadir, Dzarfan (Universiti Utara Malaysia, 2005)
Independent auditing is an important attribute for efficient capital markets.However, due to the recent corporate scandals in the United States, the regulators are very concerned with the potential threats to the auditor independence such as the provision of management advisory and other non-audit services (NAS) by auditors to their audit client.Thus, specifically, the objectives of this study are to examine the impact of non-audit services, audit partner tenure, and new audit towards the propensity of the auditor in issuing going concern opinion.We utilise logistic regression analysis in this study.The results show that there exist a negative significant relationship between new audit and going concern opinion.However, both NAS and partner tenure variables are found not to be significant.Thus, the implications of these results are discussed.